Narrative review of the dynamic strength index: Measures, normative mean values and links to common sport performance metrics - Tan, K. J. Z.; Lee, M. J. C.; Storey, A. G. (Strength and Conditioning Journal, 2025)
The Dynamic Strength Index (DSI) is a metric that aids training individualization, by measuring the degree of maximal strength that an individual is able to express dynamically, with high versus low DSI scores indicating the need for more maximal strength training versus more ballistic strength training, respectively. In this review, we (a) discuss the different DSI measures and normative mean DSI values, (b) explore the links between DSI and sport performance, and (c) assess the practical utility of using the DSI when making training decisions. The results found that most of the research has focused on measuring lower-body bilateral strength, with the countermovement jump (CMJ) and the isometric midthigh pull (IMTP) being the most common measures used due to high reliability. Although other DSI measures and calculations exist, there is limited evidence to support their practical utility. Links were found between DSI and other ballistic strength measures, but limited research has investigated the relationships between DSI and change of direction (COD). Given the relationships between several CMJ variables with COD performance, and the theoretical prominence of the slow stretch-shortening cycle (SSC) in both, there is potential for further research in this area.